PENGARUH CITRA LEMBAGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN DAN KOMITMEN RELASIONAL DAN DAMPAKNYA PADA POSITIVE WORD OF MOUTH - Kusumajaya, Robby Andika; Rivai, Alimuddin Rizal (Jurnal Ilmiah Telaah Manajemen, 2017)
This study was done to examine the influence of the institution image and service quality toward student's satisfaction and the its implication image on student relational commitment and the impacts to positive word of mouth. This study was done to STEKOM students in Semarang. The amaount of respondents were 131students. Samples were taken by purposive sampling technique based on criteria and consideration determined by researcher with software SPSS. V19. The result were ; 1. The institution image owned wholy accepted and gave positive impact to students. 2. The intense of service quality will influencepositively to a very high of students' satisfaction. 3. The high satisfaction was gained from service and institution image will influence positively to student relational commitment. 4. Relational commitment gave the close relationship among the students toward the institution was influenceful and created cooperation through positive word of mouth behaviour. Keywords: Institution Image, Service Quality, Satisfaction, Relational Commitment, Positive Word Of Mouth